The Genetic Diversity of Macroalgae on The Ekas Coast of East Lombok Based on Chromatogram Data from PCR Ampification - Baiq Repika Nurul Furqan; Imam Syahputra Yamin; Sri Sofiati Umami (Universitas Islam Negeri Mataram, 2023)
Macroalgae are multicellular photosynthetic organisms that live in water. Some species of macroalgae are very difficult to identify based on their morphology alone because they have great similarities. Therefore, identification of macroalgae diversity based on its genotype is very important to do in order to enrich the genetic information of macroalgae found on one of the beaches on the island of Lombok. This study aimed to analyze the genetic diversity of macroalgae from Pantai Ekas Beach, Jeowaru District, East Lombok, NTB using 18S rRNA gene markers. The research was carried out in 4 stages, namely sampling, morphological analysis of samples, isolation of total macroalgae DNA, isolation of genes by PCR amplification, agarose gel electrophoresis. Sampling was carried out at certain coordinates at east longitude and south latitude using the Ekas Beach quadratic transect method. The morphological analysis of the samples was guided by an identification key. Total DNA, macroalgae were isolated based on the spin column I DNA kit easy method. Genes were isolated by means of PCR amplification. Total DNA isolates and gene amplicons were confirmed by agarose gel electrophoresis. The results obtained were based on their morphology, all samples obtained were grouped into 9 macroalgae samples which could be divided into brown macroalgae (3 samples), green macroalgae (2 samples) and red macroalgae (4 samples). All samples have successfully isolated total DNA and its 18S rRNA gene which was confirmed by agarose gel electrophoresis chromatogram.